Insulin Pumps and Remote Software Updates: A New Way Forward. (March 2016) - Schaeffer, Noel E.; Parks, Linda J.; Verhoef, Erik T.; Morgan, Corey A.; Stal, Mikhail
This article discusses the future direction of insulin pump technology and its relationship to the software update process. A user needs analysis revealed that respondents wanted an insulin pump software update process to function much in the same way as smartphone updates. Users of insulin pumps have the same expectations as with other ubiquitous technology such as smartphones, tablets, and laptops. The development of a software update system within a regulated environment that meets the needs of insulin pump users by allowing optional software updates that provide access to pump improvements, feature additions, or access to algorithms that provide therapy-changing technologies is a new way forward for the management of a complicated disease that affects more than 450, 000 people using insulin pumps in the United States.